Cooling water intake system safety analysis based on impingement probability - Fu, Xiaocheng; Du, Fenglei; Huang, Xiaodong; Pei, Juan; Zhang, Zhenglou; Xing, Xiaofeng; Pu, Xiang (Frontiers in Marine Science, 2023)
The invasion or aggregation of marine lives on Cooling Water Intake System (CWIS) has gradually become an important problem affecting the safety of nuclear power plants in the context of environmental and climate changes. Based on a numerical model, the impingement probability is calculated and the impact on CWIS safety in a typical nuclear power plant with once-through cooling system, as well as its influence factors, are analyzed in this study. Results show that: (1) the impingement probability decreases rapidly with the increase of distance from CWIS. And the distance of impingement effect of nuclear power plant with six units is mainly within 1km from CWIS. (2) Impingement probability increases with the water withdrawal, and the closer with CWIS the faster the probability grows. (3) Generally, the stronger tide could lead to a decrease in impingement probability. (4) In the vicinity area of CWIS, the impingement probabilities of areas located at the upstream or downstream of CWIS along tidal flow direction are much higher than those not in these areas. (5) The increase of water depth can significantly reduce the impingement probability. The water depth of CWIS increase from 5m to 15m, the reduction of impingement probability could reach up to 30%. (6) To minimize the impingement impact on CWIS safety, several aspects should be considered. First, the CWIS of coastal nuclear power plant should be set in an area with a low aquatic biomass, strong tide, deep water, and less surface species within the range of 1km. Second, reduce the amount of cooling water withdrawal or velocity as much as possible.